Rancang Bangun Topologi Mesh Menggunakan Routing OSPF Pada Kantor Pekerjaan Umum Dan Tata Ruang Kota Gunung Sitoli - Zalukhu, Dedy Rahmat; Suriati, Suriati; Liza, Risko (Universitas Islam Negeri Sumatera Utara, 2022)
Internet technology is a technology that is currently widely used by humans to communicate and send various data over long distances quickly. In the process of sending data and communication on internet technology can not be separated from the path used, the shorter the path used, the faster the data sent, so communication will be easy. A computer network is a collection of a number of devices in the form of computers, hubs, switches, routers and other network devices that are connected to each other using certain communication media. The author designed the PUTR office in Gunungsitoli City to assist the process of work, especially on the network so that every job runs well without any disturbance. In designing this mesh topology the author uses OSPF routing where the results of the test can help in facilitating work that is directly connected to each other.Keywords: Cisco Packet Tracer, Mesh Topology, OSPF Routing